Advances in Head and Neck Cancer Pain. (August 2022) - Ye, Y.; Jensen, D.D.; Viet, C.T.; Pan, H.L.; Campana, W.M.; Amit, M.; Boada, M.D.
Head and neck cancer (HNC) affects over 890, 000 people annually worldwide and has a mortality rate of 50%. Aside from poor survival, HNC pain impairs eating, drinking, and talking in patients, severely reducing quality of life. Different pain phenotype in patients (allodynia, hyperalgesia, and spontaneous pain) results from a combination of anatomical, histopathological, and molecular differences between cancers. Poor pathologic features (e.g., perineural invasion, lymph node metastasis) are associated with increased pain. The use of syngeneic/immunocompetent animal models, as well as a new mouse model of perineural invasion, provides novel insights into the pathobiology of HNC pain. Glial and immune modulation of the tumor microenvironment affect not only cancer progression but also pain signaling. For example, Schwann cells promote cancer cell proliferation, migration, and secretion of nociceptive mediators, whereas neutrophils are implicated in sex differences in pain in animal models of HNC. Emerging evidence supports the existence of a functional loop of cross-activation between the tumor microenvironment and peripheral nerves, mediated by a molecular exchange of bioactive contents (pronociceptive and protumorigenic) via paracrine and autocrine signaling. Brain-derived neurotrophic factor, tumor necrosis factor α, legumain, cathepsin S, and A disintegrin and metalloprotease 17 expressed in the HNC microenvironment have recently been shown to promote HNC pain, further highlighting the importance of proinflammatory cytokines, neurotrophic factors, and proteases in mediating HNC-associated pain. Pronociceptive mediators, together with nerve injury, cause nociceptor hypersensitivity. Oncogenic, pronociceptive mediators packaged in cancer cell–derived exosomes also induce nociception in mice. In addition to increased production of pronociceptive mediators, HNC is accompanied by a dampened endogenous antinociception system (e.g., downregulation of resolvins and µ-opioid receptor expression). Resolvin treatment or gene delivery of µ-opioid receptors provides pain relief in preclinical HNC models. Collectively, recent studies suggest that pain and HNC progression share converging mechanisms that can be targeted for cancer treatment and pain management.